RESULTS OF GENE DIAGNOSIS OF LUMPY SKIN DISEASE IN THE DAGESTAN AND CHECHEN REPUBLICS-THE FIRST OFFICIAL CONFIRMATION OF THE DISEASE OCCURRENCE IN THE RUSSIAN FEDERATION TERRITORY - M. V. Biryuchenkova; A. M. Timina; N. G. Zinyakov; A. V. Scherbakov (Ветеринария сегодня)
In September 2015 a disease with clinical signs characteristic of lumpy skin disease (bovine contagious nodular dermatitis) was registered in cattle in the Republic of Dagestan and Republic of Chechnya. Laboratory diagnosis was carried out in the Reference Laboratory for highly dangerous animal diseases of the FGBI «ARRIAH». Lumpy skin disease virus was detected by polymerase chain reaction (PCR) in samples from the diseased animals. Sequencing of the PCR products confirmed the detected virus identification results. The above-mentioned tests were the first official confirmation of lumpy skin disease occurrence in the territory of the Russian Federation.